2022
DOI: 10.1037/pspi0000352
|View full text |Cite
|
Sign up to set email alerts
|

When alterations are violations: Moral outrage and punishment in response to (even minor) alterations to rituals.

Abstract: From Catholics performing the sign of the cross since the 4th century to Americans reciting the Pledge of Allegiance since the 1890s, group rituals (i.e., predefined sequences of symbolic actions) have strikingly consistent features over time. Seven studies (N = 4,213) document the sacrosanct nature of rituals: Because group rituals symbolize sacred group values, even minor alterations to them provoke moral outrage and punishment. In Pilot Studies A and B, fraternity members who failed to complete initiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 141 publications
2
11
0
Order By: Relevance
“…Thus, those who chose to receive Holy Communion on the hand during the pandemic could be perceived as less religious compared to those who maintained the usual form of reception of Holy Communion. This result was consistent with the theory indicating that alteration of ritual reflects a violation of values represented in the ritual (Stein et al 2021b). Moreover, Karwowski et al (2020) demonstrated that elevated social conservatism during the pandemic was predicted by higher anxiety.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, those who chose to receive Holy Communion on the hand during the pandemic could be perceived as less religious compared to those who maintained the usual form of reception of Holy Communion. This result was consistent with the theory indicating that alteration of ritual reflects a violation of values represented in the ritual (Stein et al 2021b). Moreover, Karwowski et al (2020) demonstrated that elevated social conservatism during the pandemic was predicted by higher anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…Our results partially confirmed the theory of ritual alteration as moral violation (Stein et al 2021a(Stein et al , 2021b. The subtle derogation of the out-group indicated that negativity was expressed toward those who altered the ritual but also toward those who did not alter it.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In this way, self-control problems disappear, because immoral choices are forbidden; they cannot even be considered in the first place. Consistent with these findings, the perceived morality of laws predicts willingness to comply with them (Nadler, 2005), and moral behavior is enforced by strong social norms and by moral outrage at transgressions (Rost et al, 2016;Skitka et al, 2021;Stein et al, 2021;Tetlock, 2003). When behaviors become immoral, people also gain the license to confront violators (e.g., confronting someone who is smoking inside; Rozin, 1999).…”
Section: Principle 2: Attach Moral Value To Behaviorsmentioning
confidence: 94%